Polisemie in die woordeboek — ’n kognitiewe perspektief - Swanepoel, P.H. (Lexikos, 1991)
Polysemy in the Dictionary — a Cognitive Perspective The main purpose of this article is to explicate Geeraerts’s claim (cf. Geeraerts l983b, 1990a) that prototype semantics is well suited as a basis for lexicographical metatheory. With Geeraerts’s view of prototype semantics and the metalexicographical principles expounded in Zgusta (l971) as a framework, a systematic analysis is given of various aspects of polysemy in the dictionary, e.g. the basic approach to lexical categories as classical categories, views on the prototype structure of polysemous items, the problem of monosemic prototype categories vs. polysemous prototype categories, the need for schemas, and the ways in which the multi-dimensional semantic structure of lexical categories are mapped onto dictionary entries. It is shown that Zgusta (l971) constantly relativizes his proposed lexicographical metatheory as a result of some of the basic attributes of polysemous categories, viz. their vague internal and external boundaries and their complex internal semantic structure. Keywords: lexicographical metatheory; polysemy; lexical categories; prototype semantics; prototype categories